THE NEED TO TRAIN FUTURE COMPUTER SCIENCE TEACHERS TO TEACH INFORMATION PROCESSES IN THE CONTEXT OF DIGITALIZATION OF EDUCATION - Shekerkekova, Ш.Т.; Bazarbayeva, Ү.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This article highlights the need to prepare future computer science teachers for teaching information and information processes in the context of education digitalization. Particular attention is given to the importance of improving the quality of teacher training under digital transformation. A review of relevant scientific works and literature is provided, outlining the main directions of training future computer science teachers. The paper analyzes the issues of teaching information and information processes within the school informatics curriculum, emphasizing the central role of information representation and measurement in general education. Furthermore, recommendations are proposed for integrating information processes into computer science instruction in digital learning environments. Methodological guidelines are also suggested to help future teachers foster students’ self-directed learning.